Thymosin β4 Protects against Cardiac Damage and Subsequent Cardiac Fibrosis in Mice with Myocardial Infarction - Fei Wang; Yajuan He; Naijuan Yao; Litao Ruan; Zhen Tian (Cardiovascular Therapeutics)
Background. Inflammation is a critical factor in the development and progression of myocardial infarction and cardiac fibrosis. Thymosin β4 (Tβ4) alleviates the disease process via protective antioxidant and anti-inflammatory mechanisms. Although Tβ4 has been shown to have a protective effect in myocardial infarction, its impact on cardiac fibrosis has not been well reported. In this study, we evaluated the influence of exogenous Tβ4 on myocardial infarction and cardiac fibrosis and explored the possible underlying mechanism. Methods. Real-time quantitative reverse-transcription PCR (qRT-PCR), immunohistochemistry (IHC), and Western blot were used to analyze Tβ4 expression in acute myocardial infarction (AMI) cardiac tissues. The effects of intraperitoneal adeno-associated virus-Tβ4 (AAV-Tβ4) on ligation-induced AMI in mice were studied using cardiac function parameters, and RT-PCR, Western blot, HE staining, Masson staining, and IHC were used to assess the degree of myocardial fibrosis. The effects of Tβ4 were confirmed in vitro using mouse cardiac myocytes and myofibroblasts. Results. Tβ4 was shown to be significantly elevated in mice AMI cardiac tissues. In mice, AAV-Tβ4 induced exogenous expression of Tβ4 significantly reduced oxidative damage, inflammation, cardiac dysfunction, and fibrosis. H2O2 inhibited mitophagy and increased inflammation in mouse cardiac myocytes via oxidative stress, and Tβ4 substantially reduced mitophagy inhibition and inflammasome activation in myocytes caused by H2O2. Furthermore, Tβ4 decreased cardiac myofibroblast growth and reduced TGF-β1-induced activation. Conclusions. AAV-Tβ4 induced expression of Tβ4 reduced inflammation, heart damage, and eventual fibrosis in vivo. Tβ4 helped to reduce oxidative stress, promote mitophagy, and alleviate inflammation and fibrosis. Exogenous supplementation of Tβ4 might be a promising therapeutic agent for treating myocardial infarction as well as cardiac fibrosis.